Chitosan Gel Containing Hypericum perforatum Extract Inhibiting Effect on Oxidative Stress in Burn Wounds of Rats - Pouria Khanzadeh; Maryam Hashemi; Mohsen Maleki; Farzad Hayati; Ahmadreza Mohamadnia (Iranian Journal of Veterinary Surgery, 2024)
The current study aimed to examine the impacts of topical sole and a combination of chitosan gel (Chit) and ethanolic extract (Ext) of Hypericum perforatum on inhibiting oxidative stress chain in burn wounds of Wistar rats. Three circular burn wounds on the back of the rats were induced in this study. The experimental groups included Sham, Chit, Silver Gel, Ext 5%, Ext 10%, Chit/Ext 5%, and Chit/Ext 10%. In addition to the evaluation of the healing process, total antioxidant capacity (TAC), malondialdehyde (MDA), and hydroxyproline levels were assessed. The results of the current study demonstrated that Chit/Ext treatment, especially at the 10% concentration, significantly reduced MDA, and remarkably enhanced TAC and hydroxyproline levels compared to the other groups. Based on the current study findings, it can be concluded that topical use of Chit and Ext can accelerate the healing process of second-degree burn wounds by inhibiting oxidative stress and inflammation and promoting angiogenesis and collagen production.